What makes Paris being Paris? Stereotypes, simulacra and tourism imaginaries. Issue 1 (2nd January 2019) - Gravari-Barbas, Maria
ABSTRACT: Paris imaginaries have served as inspiration for the creation of themed environments for tourism consumption in several parts of the World. These imaginaries are both the origin and the result of a stereotyped image of Paris, strongly attached to the nineteenth century, to the 'Belle Epoque' and to 'Romantic Paris'. From the hotel Paris Las Vegas, to the Ratatouille scenery at Disneyland Paris or to the residential area of Val d'Europe built near Disneyland Paris, Hausmannian Paris has indeed served as the main inspiration for Parisian simulacra all around the World. Our approach consists on of analyzing the « ingredients » of Paris stereotypes as they appear through two main Parisian tourism sceneries: Paris Las Vegas, in Las Vegas, and Ratatouille: L'Aventure Totalement Toquée de Rémy in Disneyland Paris. The paper concludes on a with the quasi-autonomisation of the Parisian tourism imaginaries which are eventually perpetuated through and thanks to the simulacra places built around the World. The paper stresses in particular on the role tourism plays on in the dissemination and perpetuation of these imaginary lands.